Architecture of the discrete sosine transformation processor for image compression systems on the losless-to-lossy circuit - V. V. Kliuchenia (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
The hardware implementations of fixed-point DCT blocks, known as IntDCT [1] and BinDCT [2], require some solutions. One of the main issues is the choice between the implementation of the conversion on FPGA, or the implementation on a digital signal processor (Digital Signal Processor, DSP). Each of the implementations has its own pros and cons. One of the most important advantages of the DSP implementation is the presence of special instructions used in DSP, in particular, the ability to multiply two numbers in one clock cycle. Therefore, with the advent of DSP, the limitation on the number of multiplications in algorithms was removed. On the other hand, when implementing a block on an FPGA, we can limit not ourselves to the bitness of the data (within reasonable limits), we have the ability to parallelize all incoming data and implement specialized computing cores for various tasks. In fact, designing multimedia systems on FPGAs reminds the design of similar systems based on the logic of a small and medium degree of integration. Such an implementation has the same limitations: a relatively small amount of available memory, the need to design basic structural elements (multipliers, divisors), etc. It is the inequality of the addition and multiplication operations when they are implemented on FPGAs that caused the search for DCT algorithms with the smallest number of factors. However, even this is not enough, since the structure of the multiplier is many times more complex than the structure of the adder, which made it necessary to look for ways to transform without using multiplications at all. This article shows how, on the basis of integer direct and inverse DCT and distributed arithmetic, to create a new universal architecture of decorrelated transform on FPGAs without multiplication operations for image transformation coding systems that operate on the principle of lossless-to-lossy (L2L), and to obtain the best experimental results in terms of hardware resources compared to comparable compression systems.